Implementasi FO Manajamen Bandwith RT Net Menggunakan Mikrotik RB941-2nd HAP LITE PPPOE - Fadilah, Muhammad; Wicaksono, Muhammad Arief; Handayanna, Frisma (Jurnal Teknologi informasi dan Ilmu Komputer, 2025)
The limited internet access in RT 03/RW 04, Kalimulya Village, Depok City, presents a significant problem that affects the community's ability to obtain essential information and online services. In this context, this research aims to design and implement an RT Net network based on MikroTik using fiber optic transmission media, which is expected to provide an effective solution for the local community's internet access needs. The method used in this study is experimental, encompassing several important steps. First, a user needs analysis was conducted to understand the extent of internet access requirements in the area. Next, the appropriate hardware, specifically the MikroTik RB941-2ND, was selected to support the designed network infrastructure. The network topology design also plays a crucial role in this methodology, where a topology diagram was created to facilitate installation and configuration. Subsequently, the system installation and configuration were carried out carefully to ensure that all devices function optimally.The results of this research indicate that the use of fiber optic networks (FO) successfully improved the speed and stability of internet access for the community. The bandwidth allocation achieved ranges from 10 Mbps to 20 Mbps per user, providing a better internet experience compared to previous solutions. Furthermore, the total bandwidth required for 150 users is estimated to reach 1,100 Mbps (1.1 Gbps), indicating that the network capacity can meet high demand. The conclusions of this study affirm that the implementation of the FO network with effective bandwidth management has successfully met the internet access needs of the community.